Sistemas magnéticos desordenados clássicos e quânticos - Salgado, Claudio Marcelo (2024)
We used the Curie-Weiss mean-field approximation to study the effects of random single-ion anisotropy and random magnetic field in the phase diagram as well as in the thermodynamic properties of the spin-7/2 Blume-Capel model. The phase diagrams are presented in the plane's temperature versus single-ion anisotropy and temperature versus magnetic field, temperature versus random parameters. The dependencies of magnetization are studied as a function of temperature and single-ion anisotropy. We explore compensation points in a system of spins represented by the Hamiltonian of Blume-Capel of spin-3 and spin-7/2, in a square lattice. Free energy and equations of state were obtained using mean field theory via Bogoliubov inequality. The second order phase transition was approached, in a narrow range of temperature values and single ion anisotropies, in addition to the existence of compensation points within this range. To deal with compensation points, through total magnetization, we used the mean field and the Monte Carlo simulation (MCS). In this way, we show the existence of compensation points via mean field and MCS. We study the effects of random and transverse single-ion anisotropy on the phase diagram and thermodynamic properties of the spin-5/2 Blume-Capel quantum model, which has been used as a method the mean field theory based on the Bogoliubov inequality for Gibbs free energy. The diagrams are displayed in space of the magnetization (m) versus temperature (τ = kBT/zJ), for various values of δy = Dy/zJ the (δx = Dx/zJ).